Review Article: Perth High Street, Archaeological Excavations, 1975-1977: Published by tayside and Fife Archaeological committee (TFAC) - Ottoway, Patrick (Proceedings of the Society of Antiquaries of Scotland, 2014)
The article reviews four fasicules relating to excavations in Perth High Street and describes them as a major event in the history of urban archaeology. Fasicule 1 deals with the excavations at 75-95 High Street and 5-10 Mill Street with three further volumes covering ceramics, metalwork and wood; textiles and leather; environmental remains and miscellaneous finds.